THE REVISED ILLNESS PERCEPTION QUESTIONNAIRE – EVALUATION OF METRIC CHARACTERISTICS OF THE CAUSES OF ILLNESS ATTRIBUTION SCALE - Pokrajac-Bulian, Alessandra; Kukić, Miljana; Mohorić, Tamara (Primenjena psihologija)
Perception of the disease directly affects behavior, coping strategies and emotional responses to disease, as well as the course of physical and mental recovery after the disease has already appeared. The aim of this study was to determine the construct and criterion validity of the Causes of Illness Attribution Scale, which examines to which factors people attribute the causes of their illness. Exploratory factor analysis, conducted on the results of people with type 2 diabetes (N = 88), lists three possible groups of factors to which people attribute the onset of their illness. This model, along with the original structure suggested by the authors, was then tested by confirmatory factor analysis on a sample of people with cardiovascular disease (N = 177). The three-factor model with a lower number of items had the best fit indices, compared to the other models. Also, these factors were in significant moderate correlation with anxiety and depression measures, which supports the criterion validity of the scale. Although according to the original structure of the questionnaire (IPQ-R) there are four possible groups of causes of the illness, our results show that the three-factor structure is more appropriate in the Croatian sample. Possible causes of illness are thus grouped into psychological factors, uncontrollable factors and general risk factors. The obtained subscales have satisfactory statistical indicators, with somewhat lower internal consistency reliability.